Analysis of effect of production costs and employment on sale of kurma salak - Hasibuan, Abdurrozzaq; Rahman Suleman, Abdul; Sri Poneni, Istu; Parinduri, Luthfi; Krianto Sulaiman, Oris (International Journal of Engineering and Technology, 2018)
The results of data analysis of research conducted obtained that the regression coefficient variable production costs of 0,505, meaning that if the variable value of production costs added by one unit then the sales will increase by 0,505. The value of variable labour regression coefficient of 1,214, meaning that if the variable value of labour plus one unit then the sales will increase by 1.214. The value of t-count > t-table, (4,516 > 2,262) for the variable cost of production this shows there is a positive and significant influence between the cost of production to sales results or it can be concluded that the initial hypothesis in this study is acceptable. the value of t-count > t-table, (4,115 > 2,262) for the labour variable this shows there is a positive and significant influence between the workforce to the sales results or it can be concluded that the initial hypothesis in this study is acceptable. Value F-count > F-table, (51.837 > 4.26). This shows there is a positive and significant influence between the variable cost of production and labour together to the sales results. The magnitude of the effect of variable cost of production and labour on sales results is 0.902 or 90.2%. This shows that the variable of produc-tion cost and labour can explain the dependent variable of the sales result at 90.2% while the rest that is equal to 9.8% is explained by other variable Î¼ (error term) which is not included in the estimation model.